Implementation of anti-dumping duties on iron and steel products: Effects on the Indonesian economy - Rofi'ah, Sunaini; Listiawati, Dewi (Nur Science Institute, 2024)
This research aims to empirically study the impact of Indonesia's anti-dumping measures on the performance of related imported products in 2011. Using the GTAP-E model, the region is divided into 9 regions and the industrial sector is grouped into 2 industries. Empirical results indicate that the imposition of a 20% Anti-Dumping Duty (BMAD) is ineffective in restricting trade from targeted countries. The GDP of non-targeted countries increased, but international trade balances correlated negatively with each BMAD imposition. Additionally, domestic prices in Indonesia appear to be high due to the implementation of BMAD, which has resulted in increased prices of iron and steel in the domestic market.